Pemanfaatan Media Teknologi dalam Pembelajaran Bahasa Arab pada Siswa Madrasah Tsanawiyah Zainul Bahar Wringin Bondowoso - Ana Fuji Lestari; Sulton Firdaus (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2026)
This study is motivated by the limited use of technological media in Arabic language learning at Islamic junior high schools, despite the rapid development of digital technology that demands more interactive learning processes. The study aims to describe the implementation of technological media in Arabic language learning and to analyze the challenges faced by teachers and students at Islamic Junior High School (MTs) Zainul Bahar Wringin Bondowoso. This research employed a qualitative approach using a case study method. The research subjects consisted of Arabic language teachers, students, and school administrators. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that technological media have been implemented in the planning, implementation, and evaluation stages of learning through digital presentation slides, instructional videos, pronunciation audio, and electronic worksheets. The study also reveals that the use of technological media not only increases students’ attention and participation in Arabic learning, but also improves their confidence in pronouncing Arabic vocabulary and sentences directly. In addition, this research found that the success of technology-based learning is influenced by teachers’ readiness in managing digital learning media flexibly according to classroom conditions. However, several obstacles remain, including limited technological facilities, unstable internet access, technical device problems, differences in students’ abilities, and limited instructional time.